Transforming Growth Factor-β and Endoglin Signaling Orchestrate Wound Healing - Valluru, Manoj; Staton, Carolyn A.; Reed, Malcolm W.; Brown, Nicola J. (Frontiers in Physiology, 2011)
Various complex signalling networks, biomechanical forces and biochemical signalling pathways in both hypoxic and non-hypoxic conditions orchestrate wound healing. Endoglin is a functional marker, a type III coreceptor for transforming growth factor (TGF-β) and an important regulator of tissue repair. Endoglin is expressed in stem cells and proliferating endothelial cells with elevated expression during hypoxia, regulating cellular functions such as proliferation and cell adhesion via Smad signalling. This review focuses on how the TGF- β family and more specifically Endoglin, regulate stem cell availability and modulate cellular behaviour within the wound microenvironment.